2007
DOI: 10.1093/brain/awm107
|View full text |Cite
|
Sign up to set email alerts
|

Beyond disgust: impaired recognition of negative emotions prior to diagnosis in Huntington's disease

Abstract: Previous studies of emotion recognition suggest that detection of disgust relies on processing within the basal ganglia and insula. Research involving individuals with symptomatic and pre-diagnostic Huntington's disease (HD), a disease with known basal ganglia atrophy, has generally indicated a relative impairment in recognizing disgust. However, some data have suggested that recognition of other emotions (particularly fear and anger) may also be affected in HD, and a recent study found fear recognition defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
132
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 42 publications
11
132
1
1
Order By: Relevance
“…Snowden et al, (2008) failed to find impairments in neutral facial discrimination in HD. Moreover, impairments were not found in premanifest HD (Johnson et al, 2007) or in symptomatic HD using neutral video clips (Dogan et al, 2013). It is unclear what may be driving the difference in results between this study and that by Snowden et al, (2008) since there is limited information on the neutral face performance results provided by Snowden et al, (2008).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Snowden et al, (2008) failed to find impairments in neutral facial discrimination in HD. Moreover, impairments were not found in premanifest HD (Johnson et al, 2007) or in symptomatic HD using neutral video clips (Dogan et al, 2013). It is unclear what may be driving the difference in results between this study and that by Snowden et al, (2008) since there is limited information on the neutral face performance results provided by Snowden et al, (2008).…”
Section: Discussionmentioning
confidence: 55%
“…However, as impairment to angry faces was also observed, the present study does not support the notion that disgust (or the neural processes subserving its recognition) is qualitatively different to other negative emotions, but accords well with recent studies reporting deficits in other negative emotion processing (specifically anger). This suggests a more universal deficit in negative emotion processing (Calder et al, 2010, Dogan et al, 2013, Henley et al, 2008, Johnson et al, 2007, Snowden et al, 2008. It should be noted however that as the present study did not use sad or fearful faces, it was not able to determine the degree of generalizability.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, several studies have documented a more general impairment encompassing several negative emotions in clinical patients or virtually all negative emotions across both pre-clinical and clinical individuals (e.g., De Gelder et al, 2008;Johnson et al, 2007;Snowden, et al, 2008). Some authors have argued that the selective impairment for disgust stimuli found in some studies may have been a consequence of item difficulty (Milders et al, 2003).…”
Section: Introductionmentioning
confidence: 99%